an PROGRAM ILUSI (IBU PEDULI MPASI) DI DESA KRENCENG, KEC. KEPUNG KAB. KEDIRI - Dewi Taurisiawati; Dwi Ertiana; Efi Indriyani (STIKES dan AKZI Karya Husada Kediri, 2022)
Many mothers do not give exclusive breastfeeding to their babies because of the mother's ignorance of the appropriate feeding of complementary foods, both the time of feeding and the selection of the menu. The purpose of this community service activity is to improve the provision of appropriate complementary foods. This community service method begins with conducting a survey to record the number of target babies, Village Consensus Deliberation (MMD), home visits for counseling to mothers and families. This activity was carried out in Krenceng Village, Kepung District, Kediri Regency on May 2, 2022– June 5, 2022. This 'Illusion' program can be carried out well because it has the support of the community and village officials, midwives and cadres. From the problems found above, an alternative problem reduction was obtained by holding several activities aimed at increasing the coverage of exclusive breastfeeding and increasing the provision of appropriate complementary food to babies.